An FGFR/AKT/SOX2 Signaling Axis Controls Pancreatic Cancer Stemness - Quan, Mei-Yu; Guo, Qiang; Liu, Jiayu; Yang, Ruo; Bai, Jing; Wang, Wei; Cai, Yaxin; Han, Rui; Lv, Yu-Qing; Ding, Li; Billadeau, Daniel D.; Lou, Zhenkun; et al. (Frontiers in Cell and Developmental Biology, 2020)
Cancer stemness is associated with high malignancy and low differentiation, as well as therapeutic resistance of tumors including pancreatic ductal adenocarcinoma (PDAC). Fibroblast growth factors (FGFs) exert pleiotropic effects on a variety of cellular processes and functions including embryonic stem cell pluripotency and cancer cell stemness via the activation of four tyrosine kinase FGF receptors (FGFRs). FGF ligands have been a major component of the cocktail of growth factors contained in the cancer stemness-inducing (CSI) and organoid culture medium. Although FGF/FGFR signaling has been hypothesized to maintain cancer stemness, its function in this process is still unclear. We report that inhibition of FGF/FGFR signaling impairs sphere-forming ability of PDAC in vitro, and knocking down FGFR1 and FGFR2 decreased their tumorigenesis abilities in vivo. Mechanistically, we demonstrated that SOX2 is down-regulated upon loss of FGFR signaling. The overexpression of SOX2 in SOX2-negative cells, which normally do not display stemness capabilities, is sufficient to induce spheroid formation. Additionally, we found that AKT phosphorylation was reduced upon FGFR signaling inhibition. The inhibition of AKT using specific pharmacological inhibitors in the context of CSI medium leads to the loss of spheroid formation associated with loss of SOX2 nuclear expression and increased degradation. We demonstrate that an FGFR/AKT/SOX2 axis controls cancer stemness in PDAC and therefore may represent an important therapeutic target in the fight against this very aggressive form of cancer.